Penerapan Taksonomi Bloom dalam Pembelajaran IPA SDI Permata Hati - Ina Magdalena; Evi Nudriyah; Larasati Larasati; Lisa Septi Wahyuni (RC-INSTITUT, 2020)
There are three components that are considered important in the world of education or teaching, namely, objectives, methods, evaluation. The most important stage in the learning process is evaluation. The benefit of evaluation is to be able to know the achievement of learning objectives and vice versa learning objectives are a reference in carrying out evaluations using Bloom's Taxonomy theory. Bloom's Taxonomy is a level in identifying student skills from the basic to the highest levels. Education can be done through teaching and training efforts by educators. In this case, 3 domains that make reference in education are as follows: (1) Cognitive Domain, (2) Affective Domain, (3) Psychomotor Domain.